Very low frequency of the lactase persistence allele LCT-13910T in the Armenian population - Stefan Németh; Gernot Kriegshäuser; Kristine Hovhannesyan; Hasmik Hayrapetyan; Christian Oberkanins; Tamara Sarkisian (Taylor & Francis Group, 2022)
Primary lactose malabsorption is characterised by a down-regulation of lactase activity after weaning and inability to digest lactose in adulthood. It has been suggested that the historical introduction of dairying led to a positive selection for lactase persistence variants in a regulatory region upstream of the LCT gene. Here, we genotyped 202 Armenian subjects for LCT-13910T, a lactase persistence variant which is widespread in Europeans. The homozygous C/C genotype associated with primary hypolactasia, the heterozygous C/T and the homozygous T/T lactase persistence genotypes were found in 191 (94.6%), 11 (5.4%), and 0 (0.0%) samples, respectively. The frequency for the LCT-13910*T allele was 2.7%. The observed allele frequency of 2.7% for LCT-13910T is even lower than previously reported and supports current phenotypic data about lactose malabsorption in Armenia.